Analysis of Mortality Risk in Stroke Patients for Optimizing Stroke Services - Amalia, Lisda; Islami, Aditya (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Introduction: The high mortality rate due to stroke causes a burden on health services, so it is essential to optimize stroke services. Mortality is one of the parameters used to assess stroke services. Hasan Sadikin General Hospital, as a stroke service support hospital, should carry out comprehensive service development, one of which is through continuous evaluation regarding the mortality rate of stroke patients being treated. This study aims to analyze the description of mortality in stroke patients at Hasan Sadikin General Bandung, Indonesia. Subject and Methods: The study used a retrospective analytic method for stroke patients in the Neurology ward from January to April 2023. The patients were divided into two groups: those who died and those who returned home with improvement. Data were taken from medical records regarding age, onset, length of stay, NIHSS, initial leukocytes, NLR, and complications. The data were then analyzed using the Mann-Whitney correlation test. Results: From this study showed that 22 patients died, and 70 patients were discharged with improvement. There were no statistically significant differences (p>0.05) in the variables of age, onset, and length of stay in the two groups. There were statistically significant differences (p